Apremilast effectively inhibits TNFα‐induced vascular inflammation in human endothelial cells. (13th November 2021) - Otto, M.; Dorn, B.; Grasmik, T.; Doll, M.; Meissner, M.; Jakob, T.; Hrgovic, I.
Abstract: Background: Patients with chronic inflammatory diseases (e.g. psoriasis and rheumatoid arthritis) are at increased risk for the development of atherosclerosis and cardiovascular diseases (CVD). Previous studies have suggested that phosphodiesterase 4 (PDE4) inhibitors possess anti‐inflammatory properties. Objectives: Here we examined the effect of the PDE4 inhibitor apremilast, a well‐established anti‐psoriatic drug, on pro‐inflammatory responses in TNFα‐activated endothelial cells. Methods: Human umbilical vein endothelial cells (HUVEC) were treated with tumour necrosis factor‐α (TNFα) in the presence or absence of apremilast. Expression levels of pro‐inflammatory cytokines, chemokines and adhesion molecules were assessed by ELISA, western blot and RT‐PCR. Effects of apremilast on adhesion and transendothelial migration (TEM) of THP‐1 monocytic cells were analysed in transwell assays. Results: Apremilast suppressed TNFα‐induced expression and secretion of important endothelial and monocytic pro‐inflammatory factors, including granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), C‐X‐C motif chemokine ligand 10 (CXCL10), chemokine (C‐C motif) ligand 2 (CCL2), vascular cell adhesion molecule 1 (VCAM‐1), E‐selectin and matrix metalloproteinase‐9 (MMP9). Functionally, apremilast reduced adhesion of THP‐1 cells to activated HUVECs and TEM in response to TNFα. Mechanistically, apremilast suppressed activation of nuclear factor κB (NFκB) and mitogen‐activated protein kinases (MAPK) signalling in activated HUVECs. Furthermore, inhibition of p38, C‐Jun‐N‐terminale Kinase (JNK) and NFκB in activated HUVECs decreased expression of GM‐CSF, VCAM‐1 and E‐selectin. Additionally, apremilast decreased IL‐17A‐induced secretion of IL‐6 and CCL2. Conclusions: We demonstrate that apremilast has distinct anti‐inflammatory effects in activated HUVECs, indicating that apremilast could have the therapeutic potential to prevent higher risk for CVD in patients with chronic inflammatory diseases.